Cavity ring-down spectroscopy for atmospheric pressure plasma jet analysis. (20th August 2015) - Zaplotnik, Rok; Bišćan, Marijan; Krstulović, Nikša; Popović, Dean; Milošević, Slobodan
Abstract: Pulsed cavity ring-down spectroscopy (CRDS) is a direct absorption, highly sensitive, versatile technique suitable for the analysis of a wide range of plasmas. CRDS belongs to a wide class of cavity-enhanced spectroscopies. This work briefly describes the basic principles of CRDS and summarizes the main literature specifically related to applications for atmospheric pressure plasma jets (APPJ). Emphasis is given to the temporal resolution and pulsed character of the plasma sources. As an example we present in more detail the determination of metastable helium density in the state produced in a single-electrode atmospheric pressure plasma jet driven by a pulsed high-voltage waveform. Measured He( ) number densities ranged from near the capillary orifice to at a distance 3.5 mm downstream.